A Machine‐Learning‐Based Approach for Solving Atomic Structures of Nanomaterials Combining Pair Distribution Functions with Density Functional Theory (Adv. Mater. 13/2023). Issue 13 (29th March 2023) - Kløve, Magnus; Sommer, Sanna; Iversen, Bo B.; Hammer, Bjørk; Dononelli, Wilke
Abstract : Atomic Structure Prediction In article number 2208220, Bo B. Iversen, Bjørk Hammer, Wilke Dononelli, and co‐workers present a new machine‐learning‐based approach, which combines pair distribution functions with density functional theory, for solving atomic structures of nanomaterials.